(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Modern telecommunication systems widely use broadband high-speed communication channels, especially in the "last mile." One possible implementation of such channels is Free Space Optics (FSO) systems. Like fiber-optic systems (FTTH), FSO enables broadband data transmission using infrared (IR) wavelengths, which is why it is also referred to as "fiberless optics" or "wireless optical communication". In FSO, IR waves propagate through the atmosphere, and their energy attenuation depends on atmospheric conditions. It is generally assumed that the attenuation process consists of two components: a constant component and a variable component, which depends on atmospheric transparency determined by the current meteorological conditions in a given region. The value of the constant component for a specific region is usually known, while the variable component must be determined, as it depends on changes in atmospheric transparency due to aerosols. Thus, the main challenge in FSO design is determining the integral distribution function of kilometer attenuation (IDFKA) of IR waves. Therefore, experimental measurements of statistical data on optical wave attenuation during atmospheric propagation are conducted worldwide for different climate regions. Similar measurements have been carried out for the Tashkent region (as reported in). However, due to significant climate changes, previously conducted calculations may no longer correspond to the current atmospheric conditions. This study presents new measurement data to determine the changes in the integral distribution function of kilometer attenuation (IDFKA) of IR waves.